The Influence of Urban Morphology of Tarutung on The Resilience of Cities Following An Earthquake (International Journal of Architecture and Urbanism, 2022)
Tarutung City is the capital of North Tapanuli Regency, North Sumatra Province. Tarutung City is an earthquake-prone city, this is caused by the city's geotectonic and geological conditions which are traversed by active fault lines, namely the active Toru fault. This study aims to look at the influence of the morphology of Tarutung City on disaster response urban planning. Tarutung City is considered to have started implementing a disaster response city, but several aspects still need to be improved